2020
DOI: 10.4039/tce.2020.21
|View full text |Cite
|
Sign up to set email alerts
|

Oecanthus nigricornis(Orthoptera: Gryllidae) as the first known host ofStylogaster neglecta(Diptera: Conopidae)

Abstract: The conopid fly Stylogaster neglecta Williston (Diptera: Conopidae) is a parasitoid with no known host. We report this species as the first recorded dipteran parasitoid of Oecanthus nigricornis Walker (Orthoptera: Gryllidae) (black-horned tree crickets). We reared field-collected O. nigricornis juveniles over several months in 2017 and found that larval S. neglecta emerged from them during late July into August. We estimated the incubation period for S. neglecta larvae to be around 30 days based on the length … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
14
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
2
2

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(15 citation statements)
references
References 20 publications
1
14
0
Order By: Relevance
“…First, our finding of a sex difference (no significant effects of parasitism on female body size) are difficult to explain with differential growth. In addition, in order to reduce the effect of any differential growth between parasitised and non-parasitised crickets we sampled at the beginning of the season when S. neglecta parasitises hosts (Etzler et al 2020). To control for effects of internal parasitoid feeding on host size, our main analysis used only hosts with unhatched eggs.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…First, our finding of a sex difference (no significant effects of parasitism on female body size) are difficult to explain with differential growth. In addition, in order to reduce the effect of any differential growth between parasitised and non-parasitised crickets we sampled at the beginning of the season when S. neglecta parasitises hosts (Etzler et al 2020). To control for effects of internal parasitoid feeding on host size, our main analysis used only hosts with unhatched eggs.…”
Section: Discussionmentioning
confidence: 99%
“…Sampling took place between July 11th and July 31th 2018 (Table 1). Etzler et al (2020) found that tree crickets were only parasitised in a short time window from mid-July until early August, and the timing of our sampling was intended to collect crickets at the beginning of this period. At this point, crickets would be likely to be parasitised but not yet had time to moult, and so their body size would likely be unchanged from when they were parasitised.…”
Section: Study Sites and Sampling Methodsmentioning
confidence: 99%
See 3 more Smart Citations